Blockade of the renin–angiotensin system for the primary prevention of diabetic nephropathy. (January 2012) - Thomas, Merlin C; MacGinley, Robert
SUMMARY  There is clear evidence for the pathogenic role of the renin–angiotensin system (RAS) in the progression of diabetic kidney. Treatment with either an angiotensin-converting enzyme inhibitor or angiotensin receptor blocker have been shown to reduce proteinuria and preserve renal function in patients with diabetes and chronic kidney disease. While such data provide a strong rationale for early and sustained blockade of the RAS for the primary prevention of kidney disease, clinical trial evidence to support this goal is limited and inconsistent. By contrast, data from observational and clinical trials clearly demonstrate the primacy of blood-pressure control in the development of diabetic kidney disease, especially in hypertensive patients. Whether RAS blockade offers additional benefits for primary prevention, over-and-above blood-pressure control, remains contentious. At best, any 'independent effects'' on primary prevention are modest, and certainly not the panacea envisaged by many practitioners. However, the better tolerability, efficacy and side-effects profile of RAS blockers, and other actions on retinopathy and cardiovascular disease, means that most patients with diabetes currently receive RAS blockers as first line antihypertensive agents. The future development of more effective 'escape-proof'' regimens currently offers the best way forward to realize the hope that RAS blockade will ultimately prevent diabetic kidney disease in the clinic as effectively as it does in animal models.